Effects of subsituting Calliandra leaf meal for soybean meal on intake, digestibility, growth and feed efficiency in goats - Ebong, Cyprian; Byenkya, S.G.; Ndikumana, J. (Informa UK Limited, 1999)
Two experiments were conducted to examine the effects of substituting calliandra (Callindra calothyrsus) leaf meal (CLM) for soybean meal (SBM) on intake, digestibility, growth and feed efficiency in goats. Two male and 2 female Small East African (SEA) goats were fed elephant grass (Pennisetum purpureum) ad-libitum (1.3 X intake of previous day) and four diets (300 g d-1) consisting of 0, 50, 75 and 100 percent of CLM mixed with complementary proportion of SBM in a 4x4 latin square design in experiment 1. DMI on mixed diet was higher than that on either SBM or CLM. Dry matter digestibility did not differ (P>0.05) among diets containing CLM. Experiment 2 examined the effects of complementary levels of CLM and SBM on growth and feed efficiency in goats. Five levels (0, 25, 50, 75 and 100 percent) of CLM composed with complementary proportions of SBM were fed to 30 male intact kids in a randomised design for 10 weeks. Control animals were fed elephant grass only. Highest growth rate with most efficient feed utilization was observed in kids fed equal quantities of SBM and CLM. It was concluded that CLM is a potentially valuable subsitute for SBM in compound feeds. Compositing reduces astringency, improves palatability, digestibility and feed efficiency of the ration.